2006
DOI: 10.1534/genetics.105.053165
|View full text |Cite
|
Sign up to set email alerts
|

Retroelement Genome Painting: Cytological Visualization of Retroelement Expansions in the Genera Zea and Tripsacum

Abstract: Divergence of abundant genomic elements among the Zea and Tripsacum genera was examined cytologically and a tool kit established for subsequent studies. The LTR regions from the CRM, Huck, Grande, Prem1, Prem2/Ji, Opie, Cinful-1, and Tekay retroelement families were used as FISH probes on mitotic chromosome spreads from a ''trispecies'' hybrid containing chromosomes from each of three species: Zea mays (2n ¼ 20), Z. diploperennis (2n ¼ 20), and Tripsacum dactyloides (2n ¼ 36). Except for Tekay, which painted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…To investigate whether recombination between retrotransposons extends beyond the CRM family, we performed a preliminary analysis of full-length Opie elements that revealed recombination sites in both the LTR and polyprotein regions (Figs. S5 and S6), indicating that retrotransposon recombination is not limited to the centromere-specific CRM family, which belongs to the Ty3/gypsy group of retrotransposons, but also occurs in this Ty1/copia element that is broadly distributed along Zea chromosome arms (6). However, the high frequency of recombinations among Opie elements, combined with the efficient removal of full-length elements from their chromosomal arm locations, provides a very spotty record of Opie element evolution and makes it difficult to reconstruct the history of these elements, let alone measure the effects on retrotransposition rate for individual recombination events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether recombination between retrotransposons extends beyond the CRM family, we performed a preliminary analysis of full-length Opie elements that revealed recombination sites in both the LTR and polyprotein regions (Figs. S5 and S6), indicating that retrotransposon recombination is not limited to the centromere-specific CRM family, which belongs to the Ty3/gypsy group of retrotransposons, but also occurs in this Ty1/copia element that is broadly distributed along Zea chromosome arms (6). However, the high frequency of recombinations among Opie elements, combined with the efficient removal of full-length elements from their chromosomal arm locations, provides a very spotty record of Opie element evolution and makes it difficult to reconstruct the history of these elements, let alone measure the effects on retrotransposition rate for individual recombination events.…”
Section: Resultsmentioning
confidence: 99%
“…Lineage-specific retrotransposon amplification has been documented in several plant genomes (4)(5)(6), and appears to result from temporary relief of otherwise tight suppression of transcription. Retrotransposon transcription has been shown to be induced by tissue culture (7), microbial elicitors of plant defense responses (8), and polyploidization (9), but this temporary increase in retrotransposon transcription has not been shown to effect genome expansion of the magnitude observed in many crop plants.…”
mentioning
confidence: 99%
“…Functional centromeres of maize consist of 1-2 Mb of DNA enriched for the tandemly arranged CentC repeat and members of the centromeric retrotransposon (CR) family (12), which are widely distributed in seed plants and have been extensively characterized (13)(14)(15)(16)(17)(18). Elements belonging to the maize CR1, CR2, and CR3 subfamilies have the remarkable ability to target their integration to centromeres and thus mark the historic centromere positions (12).FISH analysis has revealed that most centromeres of teosinte, and all centromeres of other Zea species and the more distantly related genus Tripsacum, contain large amounts of CentC (19,20), suggesting that CentC-rich centromeres represent the ancestral state. In contrast, centromeres of domesticated maize display a remarkable variation of CentC content in different inbreds (19).…”
mentioning
confidence: 99%
“…FISH analysis has revealed that most centromeres of teosinte, and all centromeres of other Zea species and the more distantly related genus Tripsacum, contain large amounts of CentC (19,20), suggesting that CentC-rich centromeres represent the ancestral state. In contrast, centromeres of domesticated maize display a remarkable variation of CentC content in different inbreds (19).…”
mentioning
confidence: 99%
“…Although effective in all tested inbred lines, the application of the repetitive element cocktail for somatic karyotyping has some limitations. The presence and copy number of repetitive elements varies among maize lines (Rivin et al 1986;Kato et al 2004;Lamb and Birchler 2006) and related species . Therefore, the hybridization pattern must be determined for each line.…”
mentioning
confidence: 99%